2018
DOI: 10.1016/j.energy.2018.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Mini-grid electricity service based on local agricultural residues: Feasibility study in rural Ghana

Abstract: The Sustainable Development Goals (SDGs) are emphatic on the role of energy for development. Targets include ensuring universal access to affordable, reliable and modern energy services to the about 1.3 billion people without electricity access, and to increase substantially the share of renewable energy in the global energy mix. For remote rural communities in developing countries where grid extension is often expensive, decentralised biomass mini-grids can be a reliable electricity supply source, as it provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Financial feasibility is finally a key element, which is even more complex and which should be assessed at a local scale depending on the national economy and the incentive frameworks of each of the four countries. As an example, Arranz-Piera's study in Ghana [18] indicated that a 1000 kWe combined heat-power plant would not be economically viable under the 2018 renewable feed-in-tariff rates. To ensure the economic viability of the power plant, it would be necessary to increase the rates by 25% or subsidise a minimum of 30% of the initial investment cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial feasibility is finally a key element, which is even more complex and which should be assessed at a local scale depending on the national economy and the incentive frameworks of each of the four countries. As an example, Arranz-Piera's study in Ghana [18] indicated that a 1000 kWe combined heat-power plant would not be economically viable under the 2018 renewable feed-in-tariff rates. To ensure the economic viability of the power plant, it would be necessary to increase the rates by 25% or subsidise a minimum of 30% of the initial investment cost.…”
Section: Discussionmentioning
confidence: 99%
“…Energy potentials from agricultural residues and agro-industrial residues could be explored for present and future energy needs. In the last years, several studies have explored the potential of using crop residues to partially satisfy energy requirements, avoiding some common biofuel issues [13][14][15][16][17][18][19][20][21][22]. Specifically, in countries and regions with a dominant agricultural sector, the advantages of valorising such resources, without impacting land use or introducing negative effects on crop availability and markets, have been pointed out [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Agro-waste is primarily made up of bagasse, crop peelings, and animal manure, all of which contain a large number of carbohydrates that could be converted to fermentable sugars through the production of biogas. Many additional industrial waste materials had also been identified as a potential source for the synthesis of biogas, including effluent from oilseed mills, a slurry of rice, and cassava waste [123][124][125].…”
Section: Biogasmentioning
confidence: 99%
“…Introduces power and control strategies in three different energy system configurations.None2018 72 IndiaHOMER PRORenewable based energy system (wind, hydro) with grid extensionFeasibility and reliability analysis of microgrids for rural electrification is illustrated. Comparison of economic and reliability indices is performed in varying design scenariosPartial economic indices2018 73 United KingdomMulti-criteria decision making (multi-attribute value theory)Energy system with conventional and renewable sources with different storage projectsIntroduces a methodology based on decision making for deploying different storage systems with varying energy resources considering stakeholder viewsPartial economic and environmental indices2018 74 GhanaAnalytical model, decision making based on weightageDecentralized mini-grids based on agricultural biomassFeasibility assessment of mini-grids for rural electrification based on agricultural biomass. Impact analysis considering the socio-economic profile of the communityPartial economic indices2018 75 BrazilProbability based multi-objective optimization, Latin hypercube sampling, Monte Carlo simulationPV, wind, DG and battery-based isolated hybrid power systemUncertainty analysis based design of a hybrid renewable isolated system for rural communities.…”
Section: Appendix Amentioning
confidence: 99%